2020
DOI: 10.1155/2020/8870821
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characteristics of Coal Samples under Triaxial Unloading Pressure with Different Test Paths

Abstract: In order to understand the influence of unloading path on the mechanical properties of coal, triaxial unloading confining pressure tests with different initial confining pressure and different unloading rate were carried out. The test results show that the triaxial unloading strength of coal samples under different test conditions is lower than conventional triaxial tests, but the brittleness characteristics are more obvious. This result indicates that the coal samples are easily damaged under unloading condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Triaxial tests have been extensively employed in the investigation of deformation, failure, and mechanical behavior of coal or rock, allowing for the replication of complex stress conditions encountered in the field [8,9]. For example, Zhou et al [10] conducted a study on the failure characteristics and mechanisms of coal under different confining pressures and graded loads.…”
Section: Introductionmentioning
confidence: 99%
“…Triaxial tests have been extensively employed in the investigation of deformation, failure, and mechanical behavior of coal or rock, allowing for the replication of complex stress conditions encountered in the field [8,9]. For example, Zhou et al [10] conducted a study on the failure characteristics and mechanisms of coal under different confining pressures and graded loads.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the triaxial unloading test with the conventional triaxial compression test, a reduction in the coal specimen’s cohesive force and an increase in internal friction were noted. Moreover, Wang et al [ 10 ] analyzed how the confining pressure and unloading rate impacted crack propagation; the results indicated that under greater confining pressure, crack formation post-failure, and the rate of crack expansion, increased with higher unloading rates. Takeda et al [ 11 ] examined the semi-permeability evolution of Wakkanai mudstones during cyclic loading and unloading, emphasizing the importance of considering the applied stresses when estimating argillite semi-permeability.…”
Section: Introductionmentioning
confidence: 99%
“…The existing studies have revealed that as high as 80% of the failure strength under the corresponding confining pressure is generally selected at the unloading point [15][16][17][18]. Under the same loading and unloading stress path, (1) a higher initial confining pressure tends to lead to more energy stored in the coal body and severer damages; (2) a higher unloading rate tends to lead to less energy stored in the coal body, which is more prone to brittle failure and the more complex the damage degree [19][20][21]; Xue et al [19] indicated that the energy required for rock failure is a definite value under certain conditions and is not affected by the stress loading path. Regarding the researches on the engineering properties of excavation rock mass, in addition to the above-mentioned influencing factors, the loading axial pressure rate is also a critical factor and mainly reflects the speed of stress concentration in the construction environment.…”
Section: Introductionmentioning
confidence: 99%